Clinical work posture for the dentist A comparative study of the conventional and finger control posture - Espino, Maria Carmen C.
Dentistry requires dexterity and is therefore a profession that results in physical stress. Posture plays and essential role in the prevention of the occupational hazard of reversible and irreversible physical ailments ranging from visual problems to back problems. The quality of work produced by the dentist among other factors like skill is likewise affected by the work position he assumes in his practices. School has taught us the conventional seated work position where optimum bebefits of comfort, quality of work and protection from the hazards of physical stress are achieved. Recent studies conducted by Dr. Daryl Beach have invoked an alternative posture called the finger control posture to supplant the conventional seated work position. Dr. Beach claims that this posture is more ergonomically sound. This study is a comparison of the conventional and the finger control posture conducted on 30 clinicians. Data relative to the quality of work produced as well as resultant physical stress symptoms were gathered and evaluated. Results indicate that the finger control posture was significantly better than the conventional seated work posture.